Analisis Tingkat Kepuasan Nasabah Dengan Pendekatan Fuzzy Logic Dalam Upaya Peningkatan Kualitas Pelayanan (Studi Kasus Cujk Batuaji ) - Ndoya, Yohana; Putri, Anggia Dasa (Prosiding, 2024)
This research aims to analyze the level of customer satisfaction of CUJK Batuaji using the Fuzzy Logic approach, focusing on four main variables: service quality, product quality, price quality, and atmosphere quality. The Fuzzy Logic approach was chosen because of its flexibility in handling uncertain and ambiguous data, as well as its ability to provide a more accurate picture of customer satisfaction levels. Data is collected through surveys filled out by customers, with each variable assessed on a scale of 1 to 5. The assessment results are converted into fuzzy values and analyzed using predefined fuzzy rules. The inference process was carried out using the Mamdani method, and the final results were defuzzified to obtain a representative crisp value. The research results showed that: Service quality received a score of 78.65, which is in the "High" category; The product quality received a score of 79.37, which is also in the "High" category; Price quality scored 79.13, with the same category, namely "High"; Ambience quality, with a score of 80, is also in the "High" category. With all variables in the "High" category, the overall satisfaction level of CUJK Batuaji customers can be categorized as "Very Satisfied". Based on these findings, several recommendations are provided to maintain and improve service quality, including regular monitoring, staff training, product innovation, competitive pricing, and maintaining comfortable facilities. The Fuzzy Logic approach has proven effective in providing a comprehensive picture of customer satisfaction, which is expected to help CUJK Batuaji achieve continuous improvement in service quality.